MHD mixed convection flow of a hybrid nanofluid past a permeable vertical flat plate with thermal radiation effect - Wahid, Nur Syahirah; Md Arifin, Norihan; Khashi'ie, Najiyah Safwa; Pop, Ioan; Bachok, Norfifah; Hafidzuddin, Mohd Ezad Hafidz (Elsevier, 2022)
The magnetohydrodynamic (MHD) radiative flow of a hybrid alumina-copper/water nanofluid past a permeable vertical plate with mixed convection is the focal interest in this present work. Dissimilar to the traditional nanofluid model that considers only one type of nanoparticles, we consider the hybridization of two types of nanoparticles in this work which are alumina and copper. The governing flow and heat transfer equations are simplified to the ordinary differential equations (ODEs) with the adaptation of conventional similarity transformations which are then evaluated by the bvp4c solver (MATLAB) to generate the numerical solutions. The solutions are generated and illustrated in the form of graph to be easily observed. Although dual solutions are obtained in this study, only one solution is determined to be stable. By reducing the concentration volume of copper and increasing the magnetic and radiation parameters, the boundary layer separation can be hindered. With the occurrence of opposing flow due to the mixed convection parameter, the heat transfer can be enhanced when the concentration volume of copper is being reduced and when the magnetic and radiation parameters are being proliferated.